Implications of the Pre-Wedding Photographer Profession Perspective of the Fatwa Commission of the Indonesia Ulema Council of North Sumatra Province Decree Number: 03/KF/MUI-SU/IV/2011 Regard: Pre-Wedding Photo - Isah Wiyanda; Rahmad Efendi (Journal Equity of Law and Governance, 2024)
This study analyzes the implications of the Indonesian Ulema Council (MUI) decision regarding pre-wedding photos on the profession of photographers in North Sumatra Province Decision Number: 03/KF/MUI-SU/IV/2011 Regarding: Pre-Wedding Photos:This study aims to analyze the implications of the decision of the Fatwa Commission of the Indonesian Ulema Council (MUI) of North Sumatra Province regarding pre-wedding photos on the profession of photographers in the region. Decision Number: 03/KF/MUI-SU/IV/2011 establishes ethics and limitations for photographers in taking pre-wedding photos based on an Islamic perspective. The study employs a juridical-empirical approach with qualitative research methods to understand the impact of the decision on professional practices of photographers. Data is collected through in-depth interviews with photographers, religious scholars, and engaged couples, as well as analysis of documents related to the MUI decision. The research findings indicate that the MUI decision significantly impacts the photographer profession. Photographers must adjust their practices according to the principles set out in the MUI decision, such as avoiding poses and clothing that do not align with Islamic values. However, this decision also presents challenges for photographers in meeting diverse client demands. This study provides important insights into the relationship between religious norms and the photographer profession within a local cultural context, as well as recommendations for photographers to adapt to the MUI decision while remaining professional and respecting religious values.